High mobility and excellent thermoelectric performance monolayer ZnX2Z4 (X = In, Al, Ga; Z = S, Se, Te) materials. Issue 15 (29th March 2023) - Shi, Li; Lv, Chunyan; Wei, Haoran; Xu, Wangping; Wang, Rui; Fan, Jing; Wu, Xiaozhi
Abstract : Recently, two-dimensional (2D) layered polarized ZnIn2 S4 nanosheets have been successfully synthesized in experiments. Abstract : Recently, two-dimensional (2D) layered polarized ZnIn2 S4 nanosheets have been successfully synthesized in experiments. However, the polarized monolayers are unstable in air, which hinders their practical applications. Therefore, in this work, we proposed a new family of nonpolarized monolayers (β2 -phase) ZnX2 Z4 (X = In, Al, and Ga; Z = S, Se, and Te) by first-principles. It is confirmed that the energies of β2 -phase ZnX2 Z4 are lower than those of the polarized and β-phase ZnX2 Z4 monolayers. Moreover, these ZnX2 Z4 monolayers have not only desirable indirect band gaps but also high electron mobility (up to 10 3 cm 2 V −1 s −1 ), revealing a fascinating visible light absorption range. Furthermore, β2 -phase ZnX2 Te4 (X = In, Al, and Ga) has ultra-low lattice thermal conductivity and high ZT value (up to 0.89), suggesting that these monolayers can be good candidates for thermoelectric materials. These new 2D ternary monolayers not only effectively broaden the family of 2D materials but also provide promising candidates for optoelectronic and thermoelectric materials.